Fruits, seeds and pollen morphology of Turkish Ribes L. (Grossulariaceae) - Kendir, Gülsen; Güvenç, Ayşegül; Acar, Aydan; Çeter, Talip; Pınar, N. Münevver (Springer Science and Business Media LLC, 2014)
The pollen, seed and fruit morphology of eight Ribes species was investigated with light microscopies (LM) and scanning electron microscopies (SEM). The pollen grains of Ribes are usually radially symmetrical and isopolar, their outlines are more or less circular, obtusely quadrangular or elliptic–obtusely rectangular. The pollen grains of the genus are oblate-spheroidal with the polar axes 18.66–31.1 μm and the equatorial axes 19.48–36.67 μm. The smallest dimensions are observed in R. anatolica, and the largest in R. multiflorum. The pollen grains are usually 5-,6-,7-,8-pantoporate or 5-,6-zonocolporate or pantoaperturate with operculate aperture. Aperture membranes are generally granulate or rarely psilate. Psilate-perforate and rugulate-perforate sculpturing are observed in the Ribes species. The seeds are elliptic, broadly elliptic, ovate, ovate-lanceolate, broadly ovate and campanulate in shape among the studied species. Seed length ranges from 2 to 4 mm and seed width from 1 to 4 mm. The apex of the seeds is acute, acuminate or obtuse. The bases of the seeds are obtuse, reture and emarginated. The hilum is elliptical or ovate. They show variation in color: dark orange, dark brown, yellow, orange and light orange. Several types of ornamentations have been observed by SEM on surface structures: psilate, striate-reticulate, indistinct striate and reticulate. All species have an epigynous berry formed from inferior ovaries. The berry is usually glabrous and globose or depressed, 4–11 mm long and 5–13 mm wide and crowned with calyx remnants at the apex. The pericarp is fleshy and indehiscent with 1–23 seeds. The fruit surface is usually glabrous or rarely hispid and verrucose in LM. The colors of the fruits vary between red with light thin bands, dark red with light thin bands, yellow or purplish red with light thick bands, orange-red and black. The surface of the berry is reticulate or indistinctly reticulate in SEM. Simple glandular trichomes have been observed in R. nigrum, R. uva-crispa and R. multiflorum. Ornamentations, pollen shape, aperture type, fruit and seed shape and color have been observed as important morphological characters.
Keywords: 2. Zero hunger